The loudest voice in the room how the brilliant, bombastic Roger Ailes built Fox News and divided a country - Sherman, Gabriel (Random House, 2017)
An inside account of Fox News offers insight into its operations and influence, covering the original launch of the cable news network by Roger Ailes and Rupert Murdoch and the ways in which Fox has become a dominant force in American politics
Keywords: Ailes, Roger; Ailes, Roger -- 1940-2017; Fox News; Fox Broadcasting Company; Television broadcasting of news / United States; Television and politics / United States; USA; Biografie